Physical science - Williams, George A.; Bolen, Max C.; Doerhoff, Ray B. (New York : McGraw-Hill, 1973)
A physical science text, stressing an awareness of the environment, with related laboratory activities to lead the student into discovering basic laws and concepts of physics and chemistry.
Keywords: Science -- Juvenile literature; Physics -- Juvenile literature; Chemistry -- Juvenile literature